MECHANICAL PROPERTIES OF FLY ASH STABILIZED CLAYEY LATERITE (International Journal of Engineering and Computer Science, 2017)
Most of the Niger Delta area in Nigeria are undergoing rapid industrialization.Transportation demands are on the increase, requiring long lasting pavements. Laterites are generallybeing used for most embankments and road fills. However, in areas of the clayey laterites, not meetingspecification, it will be cheaper to stabilize insitu instead of importing laterite. This paper presents the useof fly ash to stabilize the laterite to produce cement treated road base and roller compacted concrete(RCC) without cement